2020
DOI: 10.3390/ijms21093210
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Integrin Activation of PLD2-Deficient Platelets Accelerates Inflammation after Myocardial Infarction

Abstract: Background: Phospholipase (PL)D1 is crucial for integrin αIIbβ3 activation of platelets in arterial thrombosis and TNF-α-mediated inflammation and TGF-β-mediated collagen scar formation after myocardial infarction (MI) in mice. Enzymatic activity of PLD is not responsible for PLD-mediated TNF-α signaling and myocardial healing. The impact of PLD2 in ischemia reperfusion injury is unknown. Methods: PLD2-deficient mice underwent myocardial ischemia and reperfusion (I/R). Results: Enhanced integrin αIIbβ3 activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Thus, our study comparing the outcome of AMI under acute and chronic thrombocytopenia in mice provides a first hind for the different results published by different groups. Besides, different results from our group published in the last years indicate that alterations in the inflammatory response alone are not sufficient to effect infarct size or left ventricular function after AMI [ 57 , 58 ]. However, further investigations are necessary to analyze the impact of thrombocytopenia on AMI and to improve the prognosis of patients with AMI and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our study comparing the outcome of AMI under acute and chronic thrombocytopenia in mice provides a first hind for the different results published by different groups. Besides, different results from our group published in the last years indicate that alterations in the inflammatory response alone are not sufficient to effect infarct size or left ventricular function after AMI [ 57 , 58 ]. However, further investigations are necessary to analyze the impact of thrombocytopenia on AMI and to improve the prognosis of patients with AMI and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…PLD2 is expressed in cardiomyocytes and contributes to the development of several cardiac disorders by regulating inflammatory responses [ 14 ]. However, the involvement of PLD2 in the pathogenesis of SICM remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is a key intracellular signaling effector protein required for cellular resistance to microbial invasion and inflammatory responses [ 11 , 12 ]. It primarily localizes to sarcolemmal membranes [ 13 ] and is involved in the development of numerous cardiac disorders such as ischemia–reperfusion damage [ 14 ], congestive heart failure [ 15 ], and cardiac hypertrophy [ 16 ]. However, the role of PLD2 in SICM has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Proteome studies have revealed the presence of DGKZ in human but not mouse platelets, but did not detect PLD2 in the platelets of either species (33,34). Nonetheless, functional studies indicate that human (35) or mouse (36) platelets and in in vitro differentiated mouse MKs (37) express PLD2. The log2 mean expression value of PLD2 was low in all D7 to D14 cell subsets (between 5 and 6); in contrast, DGKZ expression increased 4-fold from D7 to D14 in productive cells, in agreement with its reported presence in platelets (Supplemental Figure 12).…”
Section: The Differential Expression Profiles Point To a Key Regulatory Role Of Mtorcs During Mk Differentiationmentioning
confidence: 99%